Depressive Symptom Trajectories, Aging-Related Stress, and Sexual Minority Stress Among Midlife and Older Gay Men: Linking Past and Present. (May 2016) - Wight, Richard G.; Harig, Frederick; Aneshensel, Carol S.; Detels, Roger
We concatenate 28 years of historical depressive symptoms data from a longitudinal cohort study of U.S. gay men who are now midlife and older ( n = 312), with newly collected survey data to analyze trajectories of depressive symptomatology over time and their impact on associations between current stress and depressive symptoms. Symptoms are high over time, on average, and follow multiple trajectories. Aging-related stress, persistent life-course sexual minority stress, and increasing sexual minority stress are positively associated with depressive symptoms, net of symptom trajectories. Men who had experienced elevated and increasing trajectories of depressive symptoms are less susceptible to the damaging effects of aging-related stress than those who experienced a decrease in symptoms over time. Intervention efforts aimed at assisting gay men as they age should take into account life-course depressive symptom histories to appropriately contextualize the health effects of current social stressors.